Effects of recycled HDPE and nanoclay on stress cracking of HDPE by correlating Jc with slow crack growth. Issue 9 (4th August 2017) - Na, Sukjoon; Nguyen, Long; Spatari, Sabrina; Hsuan, Yick G.
Abstract : The effects of recycled high density polyethylene (HDPE) and nanoclay on the stress crack resistance (SCR) of pristine HDPE were evaluated using the Notched Constant Ligament Stress (NCLS) test. The test data were analyzed by both linear elastic fracture mechanics (LEFM) and elastic plastic fracture mechanics (EPFM). The LEFM approach uses the stress intensity factor K to define the two failure mechanisms: creep and slow crack growth (SCG). In contrast, using the J ‐integral in EPFM, which emphasizes the nonlinear elastic‐plastic strain field at the crack‐tip, revealed a short‐term failure stage prior to the creep failure. In this article, a power law correlation between the fracture toughness J c and SCG was found under a plane‐strain condition. Increasing recycled HDPE content lowered the SCG resistance of pristine HDPE by decreasing J c . Adding nanoclay up to 6 wt% also decreased J c while simultaneously, lowering the stress relaxation of nanocomposites, leading to longer SCG failure times at low J values. POLYM. ENG. SCI., 58:1471–1478, 2018. © Published [2017]. This article is a U.S. Government work and is in the public domain in the USA.